Engineered nanoceria alleviates thermally induced oxidative stress in free-living Breviolum minutum (Symbiodiniaceae, formerly Clade B) - Roger, Liza M.; Russo, Joseph A.; Jinkerson, Robert E.; Giraldo, Juan Pablo; Lewinski, Nastassja A. (Frontiers in Marine Science, 2022)
The breakdown of symbiotic mutualism between cnidarian hosts and dinoflagellate algae partners (i.e., bleaching) has been linked to an immune-like response pathway brought on by a nitro-oxidative burst, a symptom of thermal stress. Stress induced by reactive oxygen species (ROS)/reactive nitrogen species is a problem common to aerobic systems. In this study, we tested the antioxidant effects of engineered poly(acrylic acid)-coated cerium dioxide nanoparticles (CeO2, nanoceria) on free-living Symbiodiniaceae (Breviolum minutum), a dinoflagellate alga that forms symbiotic relationships with reef-building corals and anemones. Results show that poly(acrylic acid)-coated CeO2 with hydrodynamic diameters of ~4 nm are internalized by B. minutum in under 30 min and subsequently localized in the cytosol. Nanoceria exposure does not inhibit cell growth over time, with the treated cultures showing a similar growth trend over the 25-day exposure. Aerobic activity and thermal stress when held at 34°C for 1 h (+6°C above control) led to increased intracellular ROS concentration with time. A clear ROS scavenging effect of the nanoceria was observed, with a 5-fold decrease in intracellular ROS levels during thermal stress. The nitric oxide (NO) concentration decreased by ~17% with thermal stress, suggesting the rapid involvement of NO scavenging enzymes or proteins within 1 h of stress onset. The presence of nanoceria did not appear to influence NO concentration. Furthermore, aposymbiotic anemones (Exaiptasia diaphana, ex Aiptasia pallida) were successfully infected with nanoceria-loaded B. minutum, demonstrating that inoculation could serve as a delivery method. The ability of nanoceria to be taken up by Symbiodiniaceae and reduce ROS production could be leveraged as a potential mitigation strategy to reduce coral bleaching.